Transcription Interference and ORF Nature Strongly Affect Promoter Strength in a Reconstituted Metabolic Pathway - Carquet, Marie; Pompon, Denis; Truan, Gilles (Frontiers in Bioengineering and Biotechnology, 2015)
Fine tuning of individual enzyme expression level is necessary to alleviate metabolic imbalances in synthetic heterologous pathways. A known approach consists of choosing a suitable combination of promoters, based on their characterized strengths in model conditions. We questioned whether each step of a multiple-gene synthetic pathway could be independently tunable at the transcription level. Three open reading frames, coding for enzymes involved in a synthetic pathway were combinatorially associated to different promoters on an episomal plasmid in Saccharomyces cerevisiae. We quantified the mRNA levels of the three genes in each strain of our generated combinatorial metabolic library. Our results evidenced that the ORF nature, position, and orientation induce strong discrepancies between the previously reported promoters’ strengths and the observed ones. We conclude that, in the context of metabolic reconstruction, the strength of usual promoters can be dramatically affected by many factors. Among them transcriptional interference and ORF nature seem to be predominant.